Instrument Development for Measuring the Satisfaction Level from Service Provided by Administrative Staff of FMIPA UNNES - Aditya Marianti; Woro Sumarni; Aji Purwinarko; Amidi Amidi (Universitas Negeri Semarang, 2021)
This research aims to develop a valid and reliable measuring instrument to measure the satisfaction level from service provided by the administrative staff of FMIPA UNNES, as an effort to improve the service quality of higher education institutions. A research and development model, ADDIE, was applied in this research. Developed instruments were 20 questions that represented certain indicators, which were derived from 5 dimensions (1) tangible, (2) responsiveness, (3) reliability, (4) assurance, and (5) emphaty. Construct validity of the questioner was assessed by 2 experts and analysed using Confirmatory Factor Analysis (CFA). Internal reliability of the instruments was measured using Alfa Cronbach coefficient. These developed instruments were tested on 531 respondents that represented the user of the service. Results from expert testing stated that the instruments were proper for use with revisions. CFA results showed that all loading factors scored above 0.3 on path diagram. According to these results, the score for goodness of fit and measurement model fit were considered fulfilled. The alpha score for internal reliability analysis was 0,98 or was considered has high reliability. The conclusion of this research is the measuring instrument for satisfaction level of service provided by the administrative staff of FMIPA UNNES is valid and reliable.